A proven reoffending study of individuals managed under the multi-agency public protection arrangements (MAPPA) in England and Wales - Lundrigan, Samantha; Mann, Natalie; Specht, David; Kamitz, Lea C. (Frontiers in Psychology, 2024)
Introduction Past research into the effectiveness of multi-agency public protection arrangements (MAPPA) in reducing reoffending it limited. Thus, the current study aimed to evaluate proven reoffending patterns for MAPPA managed individuals. Methods Proven reoffending for 39,501 MAPPA managed individuals was investigated by (1) examining patterns in the timing and frequency of proven reoffending for MAPPA managed individuals; (2) examining 1-, 3-, and 5-year proven reoffending patterns of MAPPA managed individuals by MAPPA category, age, and gender; and (3) comparing crime harm levels and recall to custody for MAPPA managed individuals pre- and post-MAPPA adoption. Results Taken together, our findings show that proven reoffending rates for individuals managed under MAPPA are substantially lower than those reported in proven reoffending statistics for England and Wales. Discussion Our results suggest that MAPPA is making a positive contribution to a managing individuals convicted of sexual and violent offenses. Additionally, our findings provide the best evidence to date that MAPPA management may also be effective at reducing less serious offenses which do not typically involve immediate removal from society. These findings are considered in light of their theoretical and practical implications while potential limitations and avenues for future research are outlined.